2014
DOI: 10.1002/ange.201400400
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Conductance of Engineered Protein Nanopores through Concerted Loop Motions

Abstract: Protein nanopores have attracted much interest for nucleic acid sequencing, chemical sensing, and protein folding at the single molecule level. The outer membrane protein OmpG from E. coli stands out because it forms a nanopore from a single polypeptide chain. This property allows the separate engineering of each of the seven extracellular loops that control access to the pore. The longest of these loops, loop 6, has been recognized as the main gating loop that closes the pore at low pH values and opens it at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
(17 reference statements)
2
17
0
Order By: Relevance
“…The shortening of the state dwell times in HS-AFM-HS with respect to electrophysiology suggests that loop-6 structural transitions occur faster than the corresponding functional state transitions, an observation that may well be explained by loop-6 temporarily hovering back and forth above the β-barrel, but not entirely occluding the ion-conduction pathway. In line with our observations and interpretation, prior NMR studies showed that loop-6 (and other loops) were highly dynamic 26,27 . The NMR relaxation dispersion data revealed that residues in loop-6 moved on sub-millisecond time scales 26 , which is in good agreement with the time scales of loop-6 motions observed by HS-AFM-HS.…”
Section: Hs-afm Imaging Ofsupporting
confidence: 92%
See 1 more Smart Citation
“…The shortening of the state dwell times in HS-AFM-HS with respect to electrophysiology suggests that loop-6 structural transitions occur faster than the corresponding functional state transitions, an observation that may well be explained by loop-6 temporarily hovering back and forth above the β-barrel, but not entirely occluding the ion-conduction pathway. In line with our observations and interpretation, prior NMR studies showed that loop-6 (and other loops) were highly dynamic 26,27 . The NMR relaxation dispersion data revealed that residues in loop-6 moved on sub-millisecond time scales 26 , which is in good agreement with the time scales of loop-6 motions observed by HS-AFM-HS.…”
Section: Hs-afm Imaging Ofsupporting
confidence: 92%
“…Silencing the motion of loop-6 by tethering it to another neighboring strand also lead to an open probability of~99% independent of the pH 21 . In addition, pinning of loop-6 to the membrane lead to an open probability of 99% 27 . Therefore, the fluctuations of loop-6 are responsible for gating.…”
mentioning
confidence: 99%
“…Lipids containing paramagnetic head groups (see, e.g. (Zhuang & Tamm, 2014)) may further enhance the use of PRE's for the study of MPs and MPCs in the future.…”
Section: Nmr On Mpcsmentioning
confidence: 99%
“…The dynamic movement of the loop 6, which moves in and out of the OmpG entrance, contributes to more than 95% of gating signal. 47, 48 Chemical modification of the OmpG proteins with biotin reagents had minimal effect on the gating behavior (Figures S2-3). …”
Section: Resultsmentioning
confidence: 99%
“…Our engineered sensor had a biotin covalently attached to the long loop 6 of OmpG. 47, 48 Proteins were detected via changes in the gating pattern when they bound to biotin. Eight biotin-binding proteins, including four streptavidin homologues and four anti-biotin antibodies were differentiated by their characteristic current gating signals.…”
mentioning
confidence: 99%